Light and scanning electron microscopic characterization of thirty endemic Fabaceae species of district Lahore, Pakistan. Issue 12 (1st September 2020) - Shaheen, Shabnum; Fateh, Rozina; Younis, Sidra; Harun, Nidaa; Jaffer, Mehwish; Hussain, Khadim; Ashfaq, Muhammad; Siddique, Riffat; Mukhtar, Hanan; Khan, Farah
Abstract: In the present study anatomical characterization of 30 species of Fabaceae endemic to Lahore, Pakistan were done under light and scanning electron microscopy. Variety of qualitative and quantitative anatomical characters like epidermal cells shapes and size, stomata types, length, and width of guard cells, subsidiary cells, trichomes, silica bodies, shapes, and their numbers were studied. Overall polygonal, irregular smooth, thick walled epidermal cells were observed at both abaxial and adaxial surfaces except Dalbergia sisso Roxb in which hexagonal epidermal cells were reported. Milletia ovelifolia Kurz. possessed the largest length of epidermal cell i.e., 273.1 μm whereas Calliandra bella Benth. showed the smallest length i.e., 76.5 μm. Average width of epidermal cells ranged from 44 to 265.5 μm. M. ovelifolia Kurz had largest width while Acacia nilotica L. had the smallest width respectively. In adaxial surface epidermal cells length ranged 317 to 46.4 μm, Glycyrriza glabra L. showed the smallest length whereas Prosopis juliflora DC. had largest length. In adaxial numbers of stomata is high as compare to the abaxial surface, mostly paracytic, anisocytic, and anomocytic stomata were observed. There is not much variations observed in trichomes of studied members. Generally non glandular, unbranched, uniserate, mulicellular bulbous base with pointed tips were reported . Oval, rounded, triangular shaped silica bodies were observed in some species. It is concluded that qualitative and quantitative anatomical variations in epidermal cells, stomata and trichomes are of good taxonomic value for the studied Fabaceae species. Abstract : Light and scanning electron microscopic characterization of family Fabaceae species were done on the basis of leaf epidermal anatomy. It also provided a systematic approach for the correct identification and differentiation of the species on the basis of anatomical characters. This information would be helpful in other scientific research fields.